Systematic review on antigens for serodiagnosis of visceral leishmaniasis, with a focus on East Africa. - Vera Kühne; Zahra Rezaei; Paul Pitzinger; Philippe Büscher (Public Library of Science (PLoS), 2019)
Background Accurate and accessible diagnosis is key for the control of visceral leishmaniasis (VL). Yet, current diagnostic tests for VL have severe limitations: they are invasive or not suitable as point of care (POC) test or their performance is suboptimal in East Africa. We analysed the antigens in the VL serodiagnostics development pipeline to identify shortcomings and to propose strategies in the development of an alternative POC test for VL in East Africa. Objectives The objective of this study was to identify and to analyse all antigens for VL serodiagnosis that have been published before 2018 in order to identify candidates and gaps in the pipeline for a new POC test in East Africa. Methods A systematic literature search was performed on PubMed for original research articles on Leishmania-specific antigens for antibody detection of VL in humans. From each article, the following information was extracted: the antigen name, test format and characteristics, its reported sensitivity and specificity and study cohort specifications. Results One hundred and seven articles containing information about 96 tests based on 89 different antigens were included in this study. Eighty six of these tests, comprising 80 antigens, were evaluated in phase I and II studies only. Only 20 antigens, all of which are native, contain a carbohydrate and/or lipid moiety. Twenty-four antigens, of which 7 are non-native, are composed of antigen mixtures. Nineteen tests, comprising 18 antigens, have been evaluated on East African specimens, of which only 2 (rK28 based immunochromatographic test and intact promastigote based indirect fluorescent antibody technique) consistently showed sensitivities above 94 and specificities above 97% in a phase III study and one in a phase II study (dot blot with SLA). Only rK28 is a non-native mixture of antigens which we consider suitable for further evaluation and implementation. Conclusions The development pipeline for an alternative serodiagnostic test for VL is almost empty. Most antigens are not sufficiently evaluated. Non-protein antigens and antigen mixtures are being neglected. We propose to expand the evaluation of existing antigen candidates and to investigate the diagnostic potential of defined non-native carbohydrate and lipid antigens for VL serodiagnosis in East Africa.